Effect of Concurrent Training on Hemodynamic Responses in Male Patients with Coronary Artery Disease - Saeid Naghibi; Mohammad Reza Kordi; Mohammad Javad Maleki; Masoud Yarmohammadi (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: Exercise training has assumed a major role in cardiac rehabilitation, mostly because of its positive effects on myocardial perfusion in patient with coronary artery disease. Improvement of peripheral vascular system and myocardial contractile function have been suggested as potential adaptations. The purpose of this study was to determine the effect of concurrent training on hemodynamic responses in patients with coronary artery disease. Materials & Methods: In this interventional and experimental study twenty four patient (50-75 years old) with coronary artery disease were selected by sample of convenience and through a directive goal oriented sampling and were randomly divided to two subgroups, experimental (n=12) and control (n=12) groups. The experimental group participated in 3 months concurrent training, 3 times/week for 60 to 80 minute at 70% to 85% of MHR and 40% to 60% of 1RM. Investigation variables were assessed at baseline and at the end of the protocol by the impedance cardiography method. Data were analyzed by T test.  Results: A significant training effect was documented by an decrease in heart rate and blood pressure at rest. Stroke volume (SV) increased from 60±8 to 81±13 ml/beats, Stroke index (SI) increased from 33±4 to 44±6 ml/beat/m2, Cardiac output (CO) increased from 4±1 to 5±1 l/min and Cardiac index (CI) increased from 2±0.5 to 3±0.5 l/min/m2 (P<0.05). Systemic vascular resistance (SVR) decreased from 1782±361 to 1540±294 dynes/sec/cm5 and Systemic vascular resistance index (SVRI) decreased from 3212±662 to 2751±558 dynes/sec/m2/cm5 (P<0.05). Conclusion: We conclude that concurrent training may improve myocardial hemodynamic responses in some patients with CAD.